Hutchison's clinical methods an integrated approach to clinical practice - Glynn, Michael; Drake, W. M.; Hutchison, Robert (Elsevier, 2012)
A textbook on clinical skills. It provides a source of learning and reference for undergraduate medical students and postgraduate doctors. It seeks to teach an integrated approach to clinical practice, so that new methods and investigations are grafted onto established patterns of clinical practice, rather than added on as something extra.